"A disease of our time": The Catholic Church's condemnation and absolution of psychoanalysis (1924–1975). Issue 2 (12th March 2018) - Foschi, Renato; Innamorati, Marco; Taradel, Ruggero
Abstract: The present paper is focused on the evolution of the position of the Catholic Church toward psychoanalysis. Even before Freud's The Future of an Illusion (1927), psychoanalysis was criticized by Catholic theologians. Psychoanalysis was viewed with either contempt or with indifference, but nonpsychoanalytic psychotherapy was accepted, especially for pastoral use. Freudian theory remained for most Catholics a delicate and dangerous subject for a long time. From the center to the periphery of the Vatican, Catholic positions against psychoanalysis have varied in the way that theological stances have varied. In the middle decades of the twentieth century, some Catholics changed their attitudes and even practiced psychoanalysis, challenging the interdict of the Holy Office, which prohibited psychoanalytic practice until 1961. During the Cold War, psychoanalysis progressively became more and more relevant within Catholic culture for two main reasons: changes in psychoanalytic doctrine (which began to stress sexuality to a lesser degree) and the increasing number of Catholic psychoanalysts, even among priests. Between the 1960s and the 1970s, psychoanalysis was eventually accepted and became the main topic of a famous speech by Pope Paul VI. This paper illustrates how this acceptance was a sort of unofficial endorsement of a movement that had already won acceptance within the Church. The situation was fostered by people like Maryse Choisy or Leonardo Ancona, who had advocated within the Church for a sui generis use of psychoanalysis (e.g., proposing a desexualized version of Freudian theories), despite warnings and prohibitions from the hierarchies of the Church.